Children and families in transition : young parents and caretakers in the Eastern Caribbean (UNICEF Barbados and the Eastern Caribbean Office Christ ChurchBB, 2009)
Highlights some of the gaps which must be filled if young parents and caregivers are to enjoy their rights as guaranteed under the Convention of the Rights of the Child and other international conventions signed by sub regional governments. Documents the significant changes which have taken place in the family within the last decade. Devotes some attention to the social circumstances of households run by children and youth, whether as a result of migration or other factors.
Bibliography: p. 57-59